ANALISIS TATANIAGA KAYU MANIS DI DESA KOTA BATU KECAMATAN WARKUK RANAU SELATAN KABUPATEN OGAN KOMERING ULU SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
Analysis of food products, Cinnamon in the village of Warkuk Sub-district Rock South of Ranau District South of OKU. This research implemented in The Village Of Kota Baru Subdistrict Of Warkuk South Of Ranau OKU Regency South. Site selection is done deliberately (purposive), with the consideration that in the village of stone town have Farming of cinnamon. . The research was carried out in November of 2017. The research method used was survey methods. Withdrawal methods examples used in this research is a method of Sampling of saturation where all data are taken as respondents, i.e. there 12 the respondents involved in food products, wood is sweet in the village of stone town. The results of this study indicate that Farmer's share received farmer on food cinnamon in the village of stone town is of 60 % and the highest marketing margins earned on merchant Gatherer village with a marketing margin amounting to Rp 7.000.